2010
DOI: 10.1017/s0950268810002141
|View full text |Cite
|
Sign up to set email alerts
|

An extensive gastroenteritis outbreak after drinking-water contamination by sewage effluent, Finland

Abstract: An inappropriate cross-connection between sewage- and drinking-water pipelines contaminated tap water in a Finnish town, resulting in an extensive waterborne gastroenteritis outbreak in this developed country. According to a database and a line-list, altogether 1222 subjects sought medical care as a result of this exposure. Seven pathogens were found in patient samples of those who sought treatment. To establish the true disease burden from this exposure, we undertook a population-based questionnaire investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 31 publications
(41 reference statements)
4
71
0
1
Order By: Relevance
“…The same author found toxigenic strains of C. difficile in 18.2% of isolates from household-stored water and no toxigenic strains in the well/borehole water samples. In 2010, Laine et al (25) reported an extensive waterborne outbreak in Finland (about 6,500 cases of gastroenteritis) due to the contamination of the community water supply by purified sewage water. Campylobacter, Salmonella enterica serovar Enteritidis, norovirus, rotavirus, Giardia, and C. difficile were isolated from patients and water samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same author found toxigenic strains of C. difficile in 18.2% of isolates from household-stored water and no toxigenic strains in the well/borehole water samples. In 2010, Laine et al (25) reported an extensive waterborne outbreak in Finland (about 6,500 cases of gastroenteritis) due to the contamination of the community water supply by purified sewage water. Campylobacter, Salmonella enterica serovar Enteritidis, norovirus, rotavirus, Giardia, and C. difficile were isolated from patients and water samples.…”
Section: Discussionmentioning
confidence: 99%
“…Laine et al (25) described an extensive waterborne gastroenteritis outbreak that occurred in the autumn of 2007 in Finland as a consequence of the accidental contamination of the drinking water network with sewage effluents from a municipal wastewater treatment plant (WWTP). C. difficile was recovered from drinking water samples and fecal specimens of symptomatic people, together with six other pathogens.…”
mentioning
confidence: 99%
“…Based on these occurrences, recycled water use in domestic properties was discouraged by the Dutch government and the distribution schemes in question are no longer in operation. In Nokia, Finland, pipes between potable water and treated sewage were found to have been crossconnected from November to December 2007 and were reported to have resulted in over 6500 illnesses [43,44]. Despite the significant presence of dual reticulation systems across the USA, very limited research into cross-connection events and cross-connection detection has been published.…”
Section: Reported Cross-connection Eventsmentioning
confidence: 99%
“…Although causative agents of this outbreak from tap water could not be isolated, (we did not receive any suspected water samples) the detection of fecal coliforms from patients' samples was consistent with local health authority report, suggesting contamination of tap water with waste water as a possible source of infection in this outbreak. Mixed enteropathogens in clinical samples of cases with gastroenteritis outbreak have already been reported in Switzerland, Finland and Chile [10][11][12]. The source of both outbreaks in Switzerland and Finland was reported to be defective waste water system and sewage contaminated drinking water due to observation of fecal coliforms, respectively.…”
Section: Discussionmentioning
confidence: 89%